2013
DOI: 10.3310/hta17180
|View full text |Cite
|
Sign up to set email alerts
|

Exercise for depression in care home residents: a randomised controlled trial with cost-effectiveness analysis (OPERA)

Abstract: Reports are published in Health Technology Assessment (HTA) if (1) they have resulted from work for the HTA programme, and (2) they are of a sufficiently high scientific quality as assessed by the reviewers and editors.Reviews in Health Technology Assessment are termed 'systematic' when the account of the search appraisal and synthesis methods (to minimise biases and random errors) would, in theory, permit the replication of the review by others. HTA programmeThe HTA programme, part of the National Institute f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 140 publications
(218 reference statements)
0
41
0
Order By: Relevance
“…That nearly half of our participants were depressed, and that only a quarter of these cases were identified as depressed in care-home records underscores the relevance of depression as an important and neglected health problem needing treatment (appendix p 2). 8 A quarter of residents were excluded by care-home managers because their health was very poor, or because of concerns that approaching the resident might cause distress (figure 2). Residents excluded because of very poor health would have been unlikely to be able to participate in the exercise groups and thus unlikely to benefit from the intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That nearly half of our participants were depressed, and that only a quarter of these cases were identified as depressed in care-home records underscores the relevance of depression as an important and neglected health problem needing treatment (appendix p 2). 8 A quarter of residents were excluded by care-home managers because their health was very poor, or because of concerns that approaching the resident might cause distress (figure 2). Residents excluded because of very poor health would have been unlikely to be able to participate in the exercise groups and thus unlikely to benefit from the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…We delivered exercise in groups to enhance adherence, increase social interaction, and reduce the cost per resident 9,10 . The exercise classes were designed to provide a moderate intensity strength and aerobic training stimulus 8 . The twice-weekly physiotherapist-led 45 min sessions ran for up to 12 months (intended length 12 months, no minimum duration) in each home and provided a moderately intense exercise stimulus via progressive aerobic and resistance training activities to be done while sitting and standing, using simple, accessible exercise equipment supported by music tracks selected for their facilitatory effects 11 .…”
Section: Methodsmentioning
confidence: 99%
“…However, guidance on the conduct of research involving people who lack capacity is often not clearly understood, even by research ethics committees 8 or easily put into practice. 9 When cluster-randomised trials are conducted in residential homes, there are additional ethical challenges, as well as statistical challenges. [10][11][12] In these trials, clusters are randomised rather than individuals themselves.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Although it was a large, adequately powered trial of a 12-month-long intervention, the OPERA trial found no detectable effect of the intervention on either the prevalence or incidence of depression [6,8]. There was also no observable effect on any of the predefined secondary outcomes.…”
Section: Introductionmentioning
confidence: 99%